Trauma-Induced Coagulopathy and Massive Bleeding: Current Hemostatic Concepts and Treatment Strategies - Gratz, Johannes; Oberladstätter, Daniel; Schöchl, Herbert (Hämostaseologie, 2020)
Hemorrhage after trauma remains a significant cause of preventable death. Trauma-induced coagulopathy (TIC) at the time of hospital admission is associated with an impaired outcome. Rather than a universal phenotype, TIC represents a complex hemostatic disorder, and standard coagulation tests are not designed to adequately reflect the complexity of TIC. Viscoelastic testing (VET) has gained increasing interest for the characterization of TIC because it provides a more comprehensive depiction of the coagulation process. Thus, VET has been established as a point-of-care-available hemostatic monitoring tool in many trauma centers. Damage-control resuscitation and early administration of tranexamic acid provide the basis for treating TIC. To improve survival, ratio-driven massive transfusion protocols favoring early and high-dose plasma transfusion have been implemented in many trauma centers around the world. Although plasma contains all coagulation factors and inhibitors, only high-volume plasma transfusion allows for adequate substitution of lacking coagulation proteins. However, high-volume plasma transfusion has been associated with several relevant risks. In some European trauma facilities, a more individualized hemostatic therapy concept has been implemented. The hemostatic profile of the bleeding patient is evaluated by VET. Subsequently, goal-directed hemostatic therapy is primarily based on coagulation factor concentrates such as fibrinogen concentrate or prothrombin complex concentrate. However, a clear difference in survival benefit between these two treatment strategies has not yet been shown. This concise review aims to summarize current evidence for different diagnostic and therapeutic strategies in patients with TIC.
Keywords: trauma-induced coagulopathy; ratio-driven hemostatic therapy; goal-directed coagulation therapy; viscoelastic testing